Unlikely bedfellows: systematic placement of Kalanchoe sect. Pumilae (Crassulaceae subfam. Cotyledonoideae) in K. subg. Kitchingia - Smith, Gideon F. (Phytotaxa, 2025)
Five subgenera are at present recognised in Kalanchoe (Crassulaceae subfam. Cotyledonoideae), with four of these being endemic to Madagascar. Although several species and hybrids of one of these endemic subgenera, K. subg. Bryophyllum, have become established—even naturalised or invasive—in mild-climate parts of the world, only representatives of the autonymic K. subg. Kalanchoe occur naturally beyond the island. To date, with a few notable exceptions, the majority of the Malagasy Kalanchoe species have been assigned to the subgenera in which they fit best. One of the species, K. pumila, the type of which is the type of K. sect. Pumilae, which thus far has not been assigned to a subgenus, is here placed in K. subg. Kitchingia.